HER+ Sustainable Land Management Trial in Ethiopia: Endline Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The HER+ Sustainable Land Management Study is a randomized controlled trial evaluating a bundled intervention that provides training and inputs (including 4-6 fruit tree seedlings, vegetable seeds, and tools) to encourage extremely poor rural Ethiopian households to adopt three complementary sustainable land management (SLM) practices: fruit tree planting, composting, and home gardening.